A CASE-CONTROL STUDY TO ASSESS THE ASSOCIATION OF ALOPECIA AREATA WITH THYROID DYSFUNCTION AND THYROID AUTOIMMUNITY - Habib, Aamir; Ansari, Mohsin Mehmood; Basra, Arslan Ahmed; Nazeer, Hafsa; Ahmed, Asfa; Shaheen, Sohail (Journal of Ayub Medical College Abbottabad, 2023)
Background: Several previous studies have suggested a positive association between Alopecia Areata and thyroid disorders. However, there is a paucity of such studies in our country. Our study aimed to know the frequency of thyroid dysfunction and thyroid autoimmunity in patients reporting to Dermatology Outdoors with Alopecia Areata (AA) and to compare it with normal controls. Methods: This was a Case-Control study conducted at the Dermatology outpatient of a tertiary care hospital in Pakistan. 102 patients with AA and 102 age and sex-matched controls were enrolled. The age of onset of the disease, the involved sites and the presence of other associated diseases were noted. Venous blood samples were taken from patients and controls for Thyroid function tests and Anti- Thyroid peroxidase antibodies (Anti-TPO Ab). The data was analyzed using Statistical Package for Social Sciences (SPSS) version 23. Results: The mean age of onset of the disease was 30.37±12.53. 91.2% of patients had the classic patch type of AA. The most commonly involved site was Scalp. Associated diseases were found in eight (7.8%) patients. Thyroid dysfunction was found in two patients and none of the Controls. Both the patients had Subclinical thyroid disease. The p-value was 0.157, which was not statistically significant. Thyroid autoimmunity (raised Anti-TPO Ab titre) was detected in five (4.90%) patients and none of the Controls. The p-value was 0.024, which was statistically significant. Conclusion: AA is significantly associated with Thyroid autoimmunity but there is no significant association between AA and clinical or subclinical thyroid disease.